The theory Y climate applied: Student driven lectures and how a high degree of student freedom can positively influence both teacher and student satisfaction in terms of learning outcomes in a typical human geography course - Ann Lise D’haen, Sarah (Improving University Science Teaching and Learning, 2023)
-